Rancang Bangun Sistem Informasi Pelayanan Publik di Desa Kadi pada Kecamatan Kota Tambolaka (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to design and build a public service information system in Kadi Village, Tambolaka City District, that can improve service quality and ease public access to information. This system is expected to accelerate administrative processes and data management, as well as facilitate interaction between the village government and its residents. The method used in developing this system is a development research (R&D) method that combines needs analysis, system design, and web-based software implementation. This information system is designed with key features such as service registration, application submission, application status checking, and efficient village administrative data management. The result of this research is a user-friendly application, accessible to the public via mobile and desktop devices, that supports transparency and accountability in public services at the village level. It is hoped that this system will make public services in Kadi Village more effective, efficient, and responsive to community needs.